2012
DOI: 10.1021/es202625r
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Thyroid Hormone Activities in Drinking Water from Eastern China: Contributions of Phthalate Esters

Abstract: Thyroid hormone is essential for the development of humans. However, some synthetic chemicals with thyroid disrupting potentials are detectable in drinking water. This study investigated the presence of thyroid active chemicals and their toxicity potential in drinking water from five cities in eastern China by use of an in vitro CV-1 cell-based reporter gene assay. Waters were examined from several phases of drinking water processing, including source water, finished water from waterworks, tap water, and boile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(53 citation statements)
references
References 53 publications
4
49
0
Order By: Relevance
“…However, it is facing water shortage and pollution problems while water demand is continually increasing due to population growth and economic development (Shi et al 2012(Shi et al , 2011. The lakes including Taihu Lake, Chaohu Lake, and Dianchi Lake and the rivers including Liaohe River, Songhua River, and Yangtze River et al have been selected as the highpoint water bodies whose pollution issues have been paid special attentions to by the Ministry of Environmental Protection since the 8th Five Year Plan period of China.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is facing water shortage and pollution problems while water demand is continually increasing due to population growth and economic development (Shi et al 2012(Shi et al , 2011. The lakes including Taihu Lake, Chaohu Lake, and Dianchi Lake and the rivers including Liaohe River, Songhua River, and Yangtze River et al have been selected as the highpoint water bodies whose pollution issues have been paid special attentions to by the Ministry of Environmental Protection since the 8th Five Year Plan period of China.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, numerous studies have shown that PAEs are widely distributed in aquatic environment and are frequently found in all sorts of waters (Shi et al 2012). In our lives, water (including drinking water and beverages) is commonly used as basic materials to maintain human life.…”
Section: Introductionmentioning
confidence: 99%
“…PAEs have http://dx.doi.org/10.1016/j.chemosphere.2014.12.063 0045-6535/Ó 2014 Elsevier Ltd. All rights reserved. been increasingly detected in municipal water supplies and groundwater, a major source of drinking water (Zhang et al, 2009;Liu et al, 2010;Shi et al, 2012). Because some PAEs are suspected endocrine-disrupting compounds, the occurrence of PAEs in water supplies has generated much attention.…”
Section: Introductionmentioning
confidence: 99%